2018
DOI: 10.3390/agriculture8030035
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Pesticide Use in Food Crop Production in Southeastern Nigeria

Abstract: Abstract:The present study examines pesticide use in producing multiple food crops (i.e., rice, yam, and cassava) and identifies the range of socio-economic factors influencing pesticide use by 400 farmers from Ebonyi and Anambra states of Southeastern Nigeria using a Tobit model. Results reveal that 68% of the farmers grew at least two food crops. Overall, 41% of the farmers applied pesticides in at least one food crop, whereas 70% of the farmers producing both rice and yam applied pesticides. Pesticide use r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 18 publications
3
11
0
3
Order By: Relevance
“…Farmers with more experience are more likely to use pesticides. 13 The present study also supports the findings of Bassi et al and Eifediyi et al that more men than women are involved in farming in Nigeria. 24 , 29…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Farmers with more experience are more likely to use pesticides. 13 The present study also supports the findings of Bassi et al and Eifediyi et al that more men than women are involved in farming in Nigeria. 24 , 29…”
Section: Discussionsupporting
confidence: 92%
“…12 According to Rahman and Chima, 70% of rice and yam farmers apply pesticides, and 41% of farmers apply pesticides to at least one food crop in Nigeria. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Biopesticides are more expensive compared with chemical pesticides. The higher the income level of farmers’ households, the higher their probability of putting in more investment and adopting biopesticides [ 52 ]. The percentage of the farmers’ household’s annual income from rice plantation measures the dependence of farmers on land.…”
Section: Methodsmentioning
confidence: 99%
“…Damage caused by pests can reach up to 80-100% in the case of agricultural treatment [61][62][63][64] for effective plant management [65][66][67][68][69][70]. The results of this study showed that we detected a highly significant difference between the genotypes in relation to the percentage of germination (Table 1).…”
Section: Influence Of Pesticides On Germination and Anthesismentioning
confidence: 58%